Questions of jurisdiction and admissibility before international courts / Yuval Shany. - Shany, Yuval (Hersch Lauterpacht memorial lectures ;, 2016)
This examination of the jurisdiction of international courts and the admissibility of cases before them analyses jurisdictional and admissibility rules in light of the roles assumed by international courts in international life and in light of the roles that jurisdictional and admissibility rules play in promoting the effectiveness and legitimacy of international courts. The theory pursued views jurisdiction as a form of delegation of power (the power to exercise judicial power and decide the law) and regards admissibility as a framework for deciding upon the propriety of exercising such power. On the basis of this theoretical framework, the author critically evaluates the exercise of judicial discretion in the existing case law of a variety of international courts, distinguishing between the category-based case selection implicit in jurisdictional rules and the case-by-case analysis and selection implicit in rules on admissibility.